Auditoría tributaria a la Cooperativa de Ahorro y Crédito matriz Fernando Daquilema en el periodo 2016 - Mónica Alexandra, Malán Ilvis (2018)
Through the Tax Audit Applied to the Cooperative of Saving and Credit Fernando Daquilema, of the Canton Riobamba, Province of Chimborazo, period 2016, with the purpose of detecting possible errors or omissions that affect the fulfillment of tax obligations and determine the reasonableness of the information presented, taking into account the Organic Law of Internal Tax Regime and its Regulations. In addition, for its development, the method of evaluating the internal control system was applied, based on COSO I, through the use of audit techniques and procedures that included a series of selective tests on the statements made and the accounting books, The character tests were selected to obtain accurate, timely and reliable information about the tax processes carried out in the entity, information that can be determined at the level of Moderate Risk of 25% and a moderate level of confidence of 75%, some values declared in The income statement forms in the source of income tax and value-added statements do not match the accounting records. It is recommended that the officers and directors of the Cooperative take into account the Final Report, in order to establish corrective actions and avoid unnecessary sanctions by the tax administration.